Statefinder Analysis of Symmetric Teleparallel Cosmology. Issue 6 (11th May 2022) - Solanki, Raja; Sahoo, Pradyumn K.
Abstract: Statefinder diagnostics is a convenient method that can differentiate between the various dark energy models. In this article, the statefinder parameters in symmetric teleparallel cosmology are analyzed. The f ( Q ) f(Q) gravity theory is an alternative theory to general relativity where gravitational interactions attribute to the non‐metricity scalar Q . In the present work, two f ( Q ) f(Q) models are considered which contains a linear and a non‐linear form of non‐metricity scalar, specifically, f ( Q ) = α Q + β Q f(Q)=α Q + β Q and f ( Q ) = α Q + β Q 2 f(Q)=α Q + β Q^2, where α and β are free parameters and then statefinder parameters ( r, s ) (r, s) are evaluated. The trajectory of the models in the r − s r-s plane are plotted. In addition, the physical behavior of different cosmological parameters such as density, deceleration, and the EoS parameters are analyzed. Further, Om diagnostic is used to differentiate the behavior of both f ( Q ) f(Q) models. It is found that both f ( Q ) f(Q) models predict that the present universe is accelerating due to the dark energy component evolving due to non‐metricity. Moreover, model I represents phantom type behavior while model II follows quintessence scenario. Abstract : In this article, a complete analysis of statefinder parameters for f ( Q ) f(Q) gravity is performed. Two f ( Q ) f(Q) models are considered, Q specifically, f ( Q ) = α Q + β Q f(Q)=α Q + β Q and f ( Q ) = α Q + β Q 2 f(Q)=α Q + β Q^2, where α and β are free model parameters. It is observed that both models predict that the present universe is accelerating and furthermore, model I represents phantom behavior while model II follows quintessence scenario.